A simple method of dating marine growth circuli on scales of wild one sea-winter and two sea-winter atlantic salmon (salmo salar) - Todd, Christopher D.; Whyte, Bryce D.M.; Maclean, Julian C.; Revie, Crawford W.; Lonergan, Michael E.; Hanson, Nora N. (Canadian Journal of Fisheries and Aquatic Sciences, 2014)
A method of dating the marine growth circuli on Atlantic salmon (Salmo salar L.) scales is presented. Data were available for 54 salmon, intercepted as smolts at the completion of their downstream migration in the River North Esk, Scotland. Smolts were tagged, released, and recaptured as return adults after either one (1SW) or two (2SW) winters at sea. Dating of circuli was achieved by fitting a simple quadratic model to the circuli pertaining to fixed points on the scale. For 1SW fish, the latter were the dates of river emigration and completion of marine migration, and the midpoint circulus (equal to the winter solstice) of the winter annulus. For 2SW salmon, these were the date of emigration and the two winter annulus midpoints. A key assumption is that winter annulus formation arises from constraints of light availability on foraging, and hence, reduced growth rate. Comparative analyses indicate the method to be robust and effectively transferable to salmon of known capture date - but of unknown smolt emigration date - by assuming a fixed date of emigration; in such cases, circuli could still be allocated with confidence to a calendar month.